Molecular condensation and mechanoregulation of plant class I formin, an integrin-like actin nucleator - Ma, Zhiming (2023)
The actin cytoskeleton (AC) undergoes rapid remodelling to coordinate cellular processes during signal transduction, including changes in actin nucleation, crosslinking, and depolymerization in a time- and space-dependent manner. Switching the initial actin nucleation often provides timely control of the entire actin network formation. Located at the cell surface, the plant class I formin family is a major class of actin nucleators that rapidly respond to exterior chemical and environmental cues. Plant class I formins are structurally integrated within the plant cell wall-plasma membrane-actin cytoskeleton (CW-PM-AC) continuum, sharing similar biophysical properties to mammalian integrins that are embedded within the extracellular matrix-PM-AC continuum. In plants, perturbation of structural components of the CW-PM-AC continuum changes the biophysical properties of two dimensional-scaffolding structures, which results in uncontrolled molecular diffusion and interactions of class I formins, as well as their clustering and activities in the nucleation of the AC. Emerging studies have shown that the PM-integrated formins are highly responsive to the mechanical perturbation of CW and AC integrity changes that tune the oligomerization and condensation of formin on the cell surface. However, during diverse signalling transductions, the molecular mechanisms that spatiotemporally underlie the mechanosensing and mechanoregulation of formin for remodelling actin remain unclear. Here, the emphasis will be placed on recent developments in understanding how the molecular condensation of class I formin regulates the biochemical activities in tuning actin polymerization during plant immune signalling, as well as how the plant structural components of the CW-PM-AC continuum control formin condensation at a nanometre scale.